The recursive core for non-superadditive games - Chen-ying Huang; Tomas Sjöström (Games, 2010)
We study the recursive core introduced in Huang and Sjöström [8]. In general partition function form games, the recursive core coalition structure may be either coarser or finer than the one that maximizes the social surplus. Moreover, the recursive core structure is typically different from the one predicted by the »-core. We fully implement the recursive core for general games, including non-superadditive games where the grand coalition does not form in equilibrium. We do not put any restrictions, such as stationarity, on strategies
Keywords: 330; coalition formation; non-cooperative implementation; partition function; recursive core